Mufradat “كَافُوْرًاۚ” Kosakata Nusantara Dalam Al-Qur’an - Abd. Muid, Fahrul; Fitrianto, Arif Rahman (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study reveals the fact that the vocabulary "kafura" is a vocabulary originating from the Nusantara culture found in the Qur'an. This study strengthens the opinion of Imam As Suyuthi in the book al-Itqan fi 'ulum al Qur'an which states that many vocabularies have been found in the Qur'an that do not originate from Arabic culture. Among them are vocabularies originating from Persian, Abyssinian, Indian, Hebrew, Syriac, Nabatean, Barbarian, Coptic, Turkish, Roman and vocabulary from the Nusantara-Indonesian-Malay languages. These loanwords appear based on the relationship between Arabic culture and non-Arab nations, resulting in cultural infiltration into the language.This study rejects the opinion of Imam Asy Syafi'I who said that the verses of the Qur'an are not mixed with foreign vocabulary at all and purely use Arabic. Syafi'I has a strong stance in rejecting the argument that there is foreign vocabulary in the Qur'an.This research is a library research using a descriptive analytical approach. The main source of this research is the results of the interpretation of Surah al-Insaan verse 5 from several interpretations including As Suyuthi, Asy Syafi'I and others. While secondary data in the form of literature from books, journals and articles related to the discussion. The methodology used in the interpretation is the maudhu'I or thematic method with an approach to the science of interpretation and history.